Analisis Nilai Moral Pada Novel The Most Wanted Girl Karya Quinwriter - Pasiha Nazwa Auniya; Zahra Azkiyah Syifa; Shiffy Asyqil Qolbi; Khaerunnisa Khaerunnisa (Universitas Palan, 2025)
This research aims to analyze the moral values ​​contained in the novel The Most Wanted Girl by Quinwriter. This novel was chosen because it is considered to represent various moral aspects that are relevant to social life. A qualitative approach was used in this research with a content analysis method to identify, categorize and interpret the moral values ​​conveyed through the characters, storyline and conflicts presented in the novel. The research results show that the moral values ​​in this novel include the values ​​of sincerity, patience, mutual help, and gratitude. Sincerity is depicted through the behavior of the main character who always tries to be open-minded about what is happening. Dispersion is shown through the characters to protect their families and communities. Please Help appears in interactions between characters who need help in the school environment, while Thanking is shown through the characters' feelings to express their pleasure. Thus, this novel not only provides entertainment, but also provides moral lessons that can be implemented in everyday life. It is hoped that this research can be a reference for readers in understanding moral values ​​in literary works and the importance of applying these values ​​in life. These findings also contribute to literary studies as an effort to preserve the educational function of a work.